Manufacturing method for all-black crystalline silicon solar cells

The PECVD deposition of a laminated film structure with SiN as the innermost layer and a gradual line width screen printing process enhances the black appearance and performance of crystalline silicon solar cells, achieving complete light absorption and uniform color consistency.

JP7600465B2Active Publication Date: 2024-12-16HENGDIAN GRP DMEGC MAGNETICS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024502542
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-23
Filing Date
2023-02-22
Publication Date
2024-12-16
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

Existing methods for manufacturing all-black crystalline silicon solar cells are limited by narrow refractive index ranges and lack of integration with various deposition processes, resulting in inadequate black appearance and performance.

Method used

A method involving PECVD deposition of a laminated film structure with SiN as the innermost layer, specific thickness and refractive index, combined with a gradual line width screen printing process to achieve complete light absorption and uniform black appearance.

Benefits of technology

The method ensures an all-black appearance with high conversion performance and uniform color consistency by optimizing light absorption and minimizing reflection, addressing limitations in existing technologies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007600465000002
    Figure 0007600465000002
  • Figure 0007600465000003
    Figure 0007600465000003
  • Figure 0007600465000001
    Figure 0007600465000001
Patent Text Reader

Abstract

This application discloses an all-black crystalline silicon solar cell, its manufacturing method and a photovoltaic module. The manufacturing method involves forming a layer of SiN on the front surface of a silicon wafer by PECVD. x The method includes the steps of: (1) depositing a film layer having a thickness of 20 nm or more, including a SiN layer, to obtain a silicon wafer with a front plated film; (2) performing backside PECVD and laser grooving on the obtained silicon wafer with a front plated film to obtain a crude silicon solar cell; and (3) performing screen printing and electrical injection on the obtained crude silicon solar cell to obtain the all-black crystalline silicon solar cell. In the manufacturing method according to the present application, a film layer is deposited on the front side of a silicon wafer by a PECVD method, and the innermost layer of SiN x Setting the material and thickness of the layer affects the absorption and reflection effects of the incident light on the cell surface, especially when the thickness is 20 nm or more, so that the incident light is almost completely absorbed and only a very small amount is reflected, resulting in an all-black silicon crystalline solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] TECHNICAL FIELD The present application relates to the technical field of batteries, for example, to a method for manufacturing an all-black crystalline silicon solar cell, in particular, to an all-black crystalline silicon solar cell, its manufacturing method and a photovoltaic module. [Background technology]

[0002] As non-renewable energy is gradually depleted and global warming becomes more and more serious, it is now common knowledge that we must establish an energy system that is dominated by renewable energy and achieve sustainable development while protecting the environment. The utilization rate of renewable energy is still insufficient and has a wide space for development. Here, photovoltaic power generation has a significant economic advantage, and its energy cost is lower than that of coal-fired electricity, and will continue to decline in the future. Its development potential should not be underestimated.

[0003] As a clean energy source, the research and development of solar energy has progressed to a new stage, and attention has been paid to the aesthetics of the appearance of the solar cell module. The all-black solar photovoltaic module is increasingly recognized for its uniform appearance and aesthetics.

[0004] To obtain an all-black module, on the one hand, the module materials can be realized by adopting auxiliary means such as black busbars, coated glass, etc., on the other hand, the key battery materials need to be well controlled by the battery production manufacturing side, which is the core of the black module. How to obtain an ideal black battery in the manufacturing process of crystalline silicon solar cells is the key to technological improvement.

[0005] CN204497240U discloses a design of a passivation anti-reflective multilayer film for a crystalline silicon high-efficiency black battery, and its contents mainly include: The bottom layer of the passivation anti-reflective multilayer film is SiO x layer, SiO x The refractive index of the layer is 1.48-1.8, the thickness is 2-20 nm, and the intermediate layer of the multi-layer passivation anti-reflective coating is SiN x layer, SiNx The layer is a single layer of SiN x Alternatively, multiple layers of SiN with different refractive indexes may be used. x The refractive index range is 1.90-2.20, the thickness is 30-70 nm, and the top layer of the passivation anti-reflection multilayer is SiO x N y layer, SiO x N y The layer has a refractive index of 1.6-1.95 and a thickness of 20-60 nm, and the passivation anti-reflection multi-layer film has a total thickness of 80-140 um and a refractive index of 1.9-2.1. The multi-layer passivation anti-reflection film of the high-efficiency black solar cell can reduce the interface state on the surface of the battery sheet, improve the passivation effect, reduce the reflectance of the surface of the battery sheet, improve the short-circuit current, and have good PID attenuation resistance properties, and the manufactured black battery has a dark and uniform color without color difference after lamination.

[0006] CN205452298U discloses a new photovoltaic black module, the contents of which mainly include the following: a glass plate, an upper encapsulant, a solar cell sheet, a lower encapsulant, a back plate, a frame coated on the edge of the glass and the back plate, which are arranged in order from top to bottom, the back plate and the frame are black, there is a silicon nitride film on the surface of the solar cell sheet, the refractive index of the silicon nitride film is 2.0-2.2, the film thickness is 60-90 nm, and the thickness of the anti-reflection film on the surface of the glass plate is 100-180 nm. The design principle of this utility model is that the thickness and refractive index of the silicon nitride film on the surface of the cell sheet are matched with the photovoltaic glass and the coating layer of the glass, and when the coating glass and the silicon nitride film layer are well matched, the appearance of the module can present a uniform color effect. The module of this utility model can meet the strict requirements for color difference of the application side, and can have high power for the module, and can also save the time and cost required for manual color subdivision, and greatly improve the work efficiency.

[0007] CN208753345U discloses an all-black BIPV module, the contents of which mainly include: a front glass with a pattern sequence block unit distributed in a matrix on the front side, a transparent PVB adhesive film for sealing the front side, a battery sheet module for realizing the conversion between solar energy and electric energy, a black PVB adhesive film for sealing the back side, and a back glass with a matte front and back side. The all-black BIPV module in this utility model can effectively realize anti-glare by adopting a front glass with a pattern sequence block unit on the front side, and can effectively match the color of the surrounding architectural environment by adopting a black PVB adhesive film on the back side, and can effectively absorb light to reduce the glare of the module. The front and back sides of the back glass are both matte surfaces, so that the BIPV module has a glare reduction effect from any angle.

[0008] Although the above technical proposals also improve the blackness of solar cells, the limitations on the refractive index in CN204497240U are extremely flawed, and the refractive index of 1.9 to 2.20 is too small. In addition, the outer layer is limited only to the requirements of the silicon oxynitride layer, and other situations such as silicon oxide layers are not mentioned. In addition, only a single plating process of PECVD (Plasma Enhanced Chemical Vapor Deposition) is used, and other processes are not included. CN205452298U and CN208753345U only improve the module, and do not mention the improvement of the cell.

[0009] Therefore, providing a method for improving the all-black appearance of solar cells is an urgent problem to be solved in the technical field of solar cells. Summary of the Invention [Problem to be solved by the invention]

[0010] The following is a brief summary of the subject matter described in greater detail in the present text. This summary does not limit the scope of the claims.

[0011] The embodiments of the present application provide an all-black crystalline silicon solar cell, its manufacturing method and photovoltaic module, in which a membrane layer is deposited on the front side of a silicon wafer by PECVD, and an innermost layer of SiN x Setting the material and thickness of the layer affects the absorption and reflection effects of the incident light on the cell surface, especially when the thickness is 20 nm or more, so that the incident light is almost completely absorbed and only a very small amount is reflected, resulting in an all-black silicon crystalline solar cell. [Means for solving the problem]

[0012] The embodiments of the present application employ the following technical solutions.

[0013] In aspect 1, there is provided a method for producing an all-black crystalline silicon solar cell, comprising the steps of: The innermost layer of the laminated structure is SiN x (1) depositing a film layer having a thickness of 20 nm or more, including a layer, to obtain a silicon wafer with a front plated film; (2) performing backside PECVD and laser grooving on the obtained silicon wafer with the front plated film to obtain a crude silicon solar cell; (3) performing screen printing and electrical injection on the obtained crude silicon solar cell to obtain the all-black crystalline silicon solar cell; How all-black crystalline silicon solar cells are made.

[0014] In the manufacturing method according to the present application, a membrane layer is deposited on the front side of a silicon wafer by PECVD, and the innermost layer of SiN x Setting the material and thickness of the layer affects the absorption and reflection effects of the incident light on the cell surface, especially when the thickness is 20 nm or more, so that the incident light is almost completely absorbed and only a very small amount is reflected, resulting in an all-black silicon crystalline solar cell.

[0015] The innermost layer of SiN in the manufacturing method according to the present application x The thickness of the layer is an important factor to control the appearance of the battery in black, when the thickness is thicker, more than 20nm, the black effect of the battery module laminated is good.

[0016] Preferably, the film layers described in step (1) are formed by stacking from the inside to the outside, and the innermost layer is a SiN x layer, intermediate SiN x layer, SiO x N y layer and SiO x The layer includes:

[0017] Preferably, the outermost layer of the membrane layer described in step (1) is SiO x The layer includes:

[0018] Preferably, the innermost layer is SiN x The layer thickness is 20 to 50 nm, and may be, for example, 20 nm, 25 nm, 30 nm, 40 nm, 45 nm, or 50 nm, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0019] Preferably, the innermost layer is SiN x The refractive index of the layer is 2.3 or more, and may be, for example, 2.3, 2.4, 2.5, 2.6, 2.7, or 2.8, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well, and is preferably 2.3 to 3.4.

[0020] The innermost layer of SiN x The refractive index of the innermost layer, SiN, is an influential factor in cell conversion efficiency. x The layer's refractive index of 2.3 or higher ensures that the solar cell has an all-black appearance as well as high conversion performance.

[0021] Preferably, the SiO xThe layer thickness is 20 nm or more, and may be, for example, 20 nm, 25 nm, 30 nm, 40 nm, 50 nm, or 60 nm, but is not limited to the numerical values ​​listed, and other numerical values ​​not listed within the numerical range apply as well, and is preferably 20 to 40 nm.

[0022] Preferably, the SiO x The refractive index of the layer is between 1.45 and 1.55, and may be, for example, 1.45, 1.47, 1.49, 1.51, 1.53, or 1.55, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0023] The SiO x The layer has a refractive index close to the low refractive index of the glass interface layer, which is 1.45 to 1.55, almost close to the refractive index of glass, which is favorable for the direct incidence absorption of light, and does not affect the refraction and reflection phenomena, greatly increases the light absorption, and makes the cell visually appear black.

[0024] Preferably, the deposition morphology described in step (1) is (a) pre-introducing silane and ammonia gases under constant pressure after evacuation; The innermost layer of SiN on the front side of the silicon wafer x (b) depositing a layer; Innermost layer SiN x On top of the layer is an intermediate SiN x Deposit a layer and an intermediate SiN x SiO layer on top x N y (c) depositing a layer; (d) pre-introducing silane and nitrous oxide under constant pressure conditions after evacuation; SiO x N y SiO layer on top x and (e) depositing a layer.

[0025] Preferably, the constant pressure described in step (a) is 200-250 Pa, and may be, for example, 200 Pa, 210 Pa, 220 Pa, 230 Pa, 240 Pa, or 250 Pa, but is not limited to the listed values, and other unlisted values ​​within the numerical range also apply.

[0026] Preferably, the time for pre-induction described in step (a) is 15 to 30 s, and may be, for example, 15 s, 18 s, 20 s, 22 s, 25 s, 28 s, or 30 s, but is not limited to the listed values, and other unlisted values ​​within the numerical range also apply.

[0027] Preferably, the pre-introduction flow rate of silane described in step (a) is 2200-2500 sccm, and may be, for example, 2200 sccm, 2250 sccm, 2300 sccm, 2400 sccm, 2450 sccm, or 2500 sccm, but is not limited to the recited values, and other unrecited values ​​within the numerical range apply as well.

[0028] Preferably, the pre-introduction flow rate of ammonia gas described in step (a) is 9000 to 9300 sccm, and may be, for example, 9000 sccm, 9050 sccm, 9100 sccm, 9200 sccm, or 9300 sccm, but is not limited to the recited numerical values, and other numerical values ​​not recited within the numerical range also apply.

[0029] Preferably, the temperature of the pre-introduction described in step (a) is 400-600°C, and may be, for example, 400°C, 450°C, 500°C, 550°C, 600°C, but is not limited to the listed values, and other values ​​not listed within the numerical range apply as well.

[0030] Preferably, the duration of deposition described in step (b) is 60-80 s, and may be, for example, 60 s, 65 s, 70 s, 75 s, or 80 s, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0031] Preferably, the temperature of deposition described in step (b) is between 400 and 600°C, for example it may be 400°C, 450°C, 500°C, 550°C, 600°C, but is not limited to the listed values, other values ​​not listed within the numerical range apply as well.

[0032] Preferably, the pressure of deposition described in step (b) is 200-250 Pa, and may be, for example, 200 Pa, 210 Pa, 220 Pa, 230 Pa, 240 Pa, or 250 Pa, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0033] Preferably, silane and ammonia gases are introduced during the deposition process described in step (b).

[0034] Preferably, the silane introduction flow rate is 2200 to 2500 sccm, and may be, for example, 2200 sccm, 2250 sccm, 2300 sccm, 2350 sccm, 2400 sccm, 2450 sccm, or 2500 sccm, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0035] Preferably, the flow rate of the ammonia gas is 9000 to 9300 sccm, and may be, for example, 9000 sccm, 9050 sccm, 9100 sccm, 9200 sccm, or 9300 sccm, but is not limited to the listed values, and other values ​​not listed within the numerical range also apply.

[0036] Preferably, the RF power of the deposition process described in step (b) is 14000-16000 W, and may be, for example, 14000 W, 14500 W, 15000 W, 15500 W, or 16000 W, but is not limited to the recited values, and other unrecited values ​​within the numerical range apply as well.

[0037] Preferably, the pulse on / off ratio of the deposition process described in step (b) is (3-5) / (50-70), and may be, for example, 3 / 50, 4 / 60, 5 / 70, 3 / 70, or 5 / 50, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0038] Preferably, the constant pressure described in step (d) is 150-200 Pa, and may be, for example, 150 Pa, 180 Pa, 200 Pa, 210 Pa, 220 Pa, 230 Pa, 240 Pa, or 250 Pa, but is not limited to the listed values, and other unlisted values ​​within the numerical range also apply.

[0039] Preferably, the time for pre-induction described in step (d) is 5 to 15 s, and may be, for example, 5 s, 8 s, 10 s, 12 s, or 15 s, but is not limited to the listed values, and other unlisted values ​​within the numerical range also apply.

[0040] Preferably, the silane pre-introduction flow rate described in step (d) is 600-700 sccm, and may be, for example, 600 sccm, 620 sccm, 640 sccm, 660 sccm, 680 sccm, or 700 sccm, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0041] Preferably, the preliminary introduction flow rate of nitrous oxide described in step (d) is 10,000 to 12,000 sccm, and may be, for example, 10,000 sccm, 10,500 sccm, 11,000 sccm, 11,500 sccm, or 12,000 sccm, but is not limited to the recited numerical values, and other numerical values ​​not recited within the numerical range also apply.

[0042] Preferably, the temperature of the pre-introduction described in step (d) is 400-600°C, and may be, for example, 400°C, 450°C, 500°C, 550°C, 600°C, but is not limited to the listed values, and other values ​​not listed within the numerical range apply as well.

[0043] Preferably, the duration of deposition described in step (e) is 150-200 s, and may be, for example, 150 s, 160 s, 170 s, 180 s, 190 s, or 200 s, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0044] Preferably, the temperature of deposition described in step (e) is between 400 and 600°C, for example it may be 400°C, 450°C, 500°C, 550°C, 600°C, but is not limited to the listed values, other values ​​not listed within the numerical range apply as well.

[0045] Preferably, the pressure of deposition described in step (e) is 100-150 Pa, and may be, for example, 150 Pa, 180 Pa, 200 Pa, 210 Pa, 220 Pa, 230 Pa, 240 Pa, or 250 Pa, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0046] Preferably, silane and nitrous oxide are introduced during the deposition process described in step (e).

[0047] Preferably, the silane introduction flow rate is 600 to 700 sccm, and may be, for example, 600 sccm, 620 sccm, 640 sccm, 660 sccm, 680 sccm, or 700 sccm, but is not limited to the listed values, and other values ​​not listed within the numerical range apply as well.

[0048] Preferably, the flow rate of the nitrous oxide is 10,000 to 12,000 sccm, and may be, for example, 10,000 sccm, 10,500 sccm, 11,000 sccm, 11,500 sccm, or 12,000 sccm, but is not limited to the listed values, and other values ​​not listed within the numerical range also apply.

[0049] Preferably, the RF power in the deposition process described in step (e) is 14000-16000 W, and may be, for example, 14000 W, 14500 W, 15000 W, 15500 W, or 16000 W, but is not limited to the recited values, and other unrecited values ​​within the numerical range apply as well.

[0050] Preferably, the pulse on / off ratio of the deposition process described in step (e) is (1-3) / (30-50), and may be, for example, 1 / 30, 2 / 40, 3 / 50, 1 / 50, or 3 / 30, but is not limited to the listed values, and other unlisted values ​​within the numerical range apply as well.

[0051] Preferably, the screen printing in step (3) is performed using a line width-graded screen.

[0052] Preferably, the line width of the graduated line width screen decreases in a gradient from the outside to the inside.

[0053] Preferably, the line width of the graduated line width screen decreases by at most 1 μm every at most 5 mm from the outer edge inward.

[0054] Every 5 mm at most may be, for example, 1 mm, 2 mm, 3 mm, 4 mm, or 5 mm, but is not limited to the listed numerical values, and other unlisted numerical values ​​within the numerical range also apply.

[0055] A reduction of at most 1 μm may be, for example, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, or 1 μm, but is not limited to the recited numerical values, and other unrecited numerical values ​​within the numerical range also apply.

[0056] Preferably, the accuracy of the line width graduated screen is ±1 μm, and may be, for example, ±0.1 μm, ±0.2 μm, ±0.5 μm, ±0.8 μm, or ±1 μm, but is not limited to the recited numerical values, and other unrecited numerical values ​​within the numerical range also apply.

[0057] In a preferred technical solution of the present application, the line width of the gradually changing screen starts from the edge and decreases by 0.5-1 μm at every 4-5 mm from 12-15 mm inward, and the line width at the starting position is 19-21 μm.

[0058] In the related art, the line width of the screen during the printing process has a difference with the line width of the actual battery, which affects the visual color of the appearance of the battery module after lamination, the narrower the line width, the blacker it is, and the wider the line width, the grayer it is. At the same time, the plating film on the back side is overflow-coated on the front side, so the periphery of the battery looks blue.

[0059] In this application, a gradient line width screen with a special line width structure is designed, and the peripheral width of the screen is widened to hide the blue appearance and form a visually black effect after lamination. This solves the problem of the blue appearance around the cell caused by plating overflow coating that is likely to occur during rear-side PECVD in step (2), and the solar cell appears completely black.

[0060] Preferably, the screen printing method described in step (3) includes: after inserting the wafer and performing grooving, performing a first print and drying, performing a second print and drying, performing a third print and drying, performing a fourth print and drying, firing, and testing the cell line width before completing the screen printing.

[0061] Preferably, the fourth print is extrusion printed using a graded line width screen.

[0062] Preferably, the line width of the graded line width screen decreases in a gradient from the outside to the inside, which means that the line width decreases in a gradient from the outermost edge of the graded line width screen to the inside.

[0063] Preferably, the line width of the graduated line width screen decreases by at most 1 μm every at most 5 mm from the outer edge inward.

[0064] Every 5 mm at most may be, for example, 1 mm, 2 mm, 3 mm, 4 mm, or 5 mm, but is not limited to the listed numerical values, and other unlisted numerical values ​​within the numerical range also apply.

[0065] A reduction of at most 1 μm may be, for example, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, or 1 μm, but is not limited to the recited numerical values, and other unrecited numerical values ​​within the numerical range also apply.

[0066] Preferably, the test error of the line width of the battery is 5 μm or less, for example, it may be 1 μm, 2 μm, 3 μm, 4 μm, or 5 μm, but is not limited to the recited values, and other unrecited values ​​in the numerical range also apply.

[0067] If the error in the line width between the cells exceeds 5 μm, the whole cell will have noticeable color skipping, which is likely to affect the visual black effect.

[0068] In a second aspect, the present embodiment provides an all-black crystalline silicon solar cell obtained by the manufacturing method described in the first aspect.

[0069] In a third aspect, the present embodiment provides a photovoltaic module including the all-black crystalline silicon solar cell according to the second aspect. Effect of the Invention

[0070] According to the above technical solutions, the beneficial effects of the embodiments of the present application are as follows:

[0071] (1) In the manufacturing method according to the embodiment of the present application, a film layer is deposited on the front surface of a silicon wafer by the PECVD method, and the innermost layer of SiN xSetting the material and thickness of the layer affects the absorption and reflection effects of the incident light on the cell surface, especially when the thickness is 20 nm or more, so that the incident light is almost completely absorbed and only a very small amount is reflected, obtaining an all-black silicon crystal solar cell with a good overall visual black effect.

[0072] (2) The solar cell not only has an all-black appearance, but also has high conversion performance.

[0073] (3) In the embodiment of the present application, a gradient line width screen with a special line width structure is designed and the printing process is adjusted to solve the problem of the surrounding area of ​​the cell appearing blue, which is caused by overflow coating of plating during rear-side PECVD. The solar cell is visually black in color, with a uniform appearance without color difference and good consistency.

[0074] Other aspects may be understood upon reading and understanding the drawings and detailed description. [Brief description of the drawings]

[0075] The drawings are intended to provide an understanding of the technical solution of the present application, constitute a part of the specification, and are intended to interpret the technical solution of the present application together with the embodiments of the present application, but are not intended to limit the technical solution of the present application.

[0076] [Figure 1] FIG. 2 is a schematic diagram showing the structure of a membrane layer according to the present application. [Diagram 2] FIG. 2 is a structural schematic diagram of the graded line width screen according to the first embodiment. [Explanation of symbols]

[0077] 1: Silicon wafer; 2: Innermost layer of SiN x Layer 3: Middle SiN x Layer;4:SiO x N y Layer;5:SiO x layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0078] The technical solution of the present application will be further described below with reference to the drawings and specific embodiments. However, the following examples are merely simple examples of the present application, and do not represent or limit the scope of the claims of the present application, and the protection scope of the present application is based on the scope of the claims. EXAMPLES

[0079] This embodiment provides a method for manufacturing an all-black crystalline silicon solar cell, and the method includes the following steps (1) to (3).

[0080] (1) A film layer is deposited on the front surface of silicon wafer 1 (LONGI silicon wafer, resistivity 0.4-1.1, thickness 160 μm, size 166 mm) by the PECVD method (Figure 1). The film layer has a laminated structure, and a silicon wafer with a front plated film is obtained. The film layer is formed from the innermost layer of SiN x Layer 2, middle SiN x Layer 3, SiO x N y Layer 4 and SiO x Layer 5 was laminated. The innermost layer was SiN x Layer 2 has a thickness of 20 nm and a refractive index of 2.3. x Layer 5 is the outermost layer and is 20 nm thick with a refractive index of 1.5.

[0081] The method for depositing the film layer includes the following steps (a) to (e).

[0082] (a) After evacuation, silane and ammonia gases were pre-introduced at a constant pressure of 230 Pa for 20 s, the silane flow rate was 2316 sccm, the ammonia gas flow rate was 9276 sccm, and the temperature was 500°C.

[0083] (b) The innermost layer of SiN on the front surface of silicon wafer 1 x Layer 2 is deposited with a deposition time of 70 s, a temperature of 500° C., a constant pressure of 240 Pa, a silane flow rate of 2316 sccm, an ammonia gas flow rate of 9276 sccm, an RF power of 14500 W, and a pulse on / off ratio of 4 / 60.

[0084] (c) Innermost layer: SiN x On top of layer 2 is a middle layer of SiN x Deposit layer 3, intermediate SiN x Layer 3: SiO x N y Layer 4 is deposited.

[0085] (d) After evacuation, silane and nitrous oxide were pre-introduced for 10 s under the conditions of a constant pressure of 180 Pa and a temperature of 500°C, with the silane flow rate being 686 sccm and the nitrous oxide flow rate being 10,990 sccm.

[0086] (e)SiO x N y Layer 4: SiO x Layer 5 was deposited with a time of 190 s, a temperature of 500° C., a constant pressure of 130 Pa, a silane flow rate of 686 sccm, a nitrous oxide flow rate of 10990 sccm, an RF power of 14500 W, and a pulse on / off ratio of 2 / 38.

[0087] (2) The resulting silicon wafer with the front plated film is subjected to backside PECVD and laser grooving to obtain crude silicon solar cells.

[0088] (3) After screen printing and electrical injection are performed on the obtained crude silicon solar cell, the all-black crystalline silicon solar cell is obtained.

[0089] The screen printing method includes putting in the wafer and grooving, then printing the first time and drying, printing the second time and drying, printing the third time and drying, and using a line width gradation type screen to print the fourth time and drying, firing, testing the line width of the battery, and then completing the screen printing.

[0090] The graduated line width screen (FIG. 2) starts at the edge and decreases in line width by 1 μm every 5 mm for 15 mm inward, with the line width at the starting position being 20 μm. EXAMPLES

[0091] This embodiment provides a method for manufacturing an all-black crystalline silicon solar cell, and the method includes the following steps (1) to (3).

[0092] (1) A film layer is deposited on the front surface of the silicon wafer 1 by the PECVD method (FIG. 1). The film layer has a laminated structure, and a silicon wafer with a front plated film is obtained. The film layer is formed from the innermost layer of SiN x Layer 2, middle SiN x Layer 3, SiO x N y Layer 4 and SiO x Layer 5 was laminated. The innermost layer was SiN x The thickness of the layer 2 is 22 nm and the refractive index is 2.5. x Layer 5 is the outermost layer and is 22 nm thick with a refractive index of 1.45.

[0093] The method for depositing the film layer includes the following steps (a) to (e).

[0094] (a) After evacuation, silane and ammonia gases were pre-introduced under the condition of a constant pressure of 250 Pa. The time was 30 s, the flow rate of silane was 2200 sccm, the flow rate of ammonia gas was 9300 sccm, and the temperature was 400°C.

[0095] (b) The innermost layer of SiN on the front surface of silicon wafer 1 x Layer 2 is deposited with a deposition time of 80 s, a temperature of 400° C., a constant pressure of 250 Pa, a silane flow rate of 2500 sccm, an ammonia gas flow rate of 9300 sccm, an RF power of 16000 W, and a pulse on / off ratio of 3 / 70.

[0096] (c) Innermost layer: SiN x On top of layer 2 is a middle layer of SiN x Deposit layer 3, intermediate SiN x Layer 3: SiO x N y Layer 4 is deposited.

[0097] (d) After evacuation, silane and nitrous oxide were pre-introduced for 15 s under the conditions of a constant pressure of 200 Pa, a temperature of 400°C, and a flow rate of silane of 700 sccm and a flow rate of nitrous oxide of 12,000 sccm.

[0098] (e)SiO x N y Layer 4: SiO x Layer 5 is deposited with a time of 200 s, a temperature of 400° C., a constant pressure of 150 Pa, a silane flow rate of 700 sccm, a nitrous oxide flow rate of 12000 sccm, an RF power of 16000 W, and a pulse on / off ratio of 1 / 50.

[0099] (2) The resulting silicon wafer with the front plated film is subjected to backside PECVD and laser grooving to obtain crude silicon solar cells.

[0100] (3) After screen printing and electrical injection are performed on the obtained crude silicon solar cell, the all-black crystalline silicon solar cell is obtained.

[0101] The screen printing method includes putting in the wafer and grooving, then printing the first time and drying, printing the second time and drying, printing the third time and drying, and using a line width gradation type screen to print the fourth time and drying, firing, testing the line width of the battery, and then completing the screen printing.

[0102] The graduated line width screen starts at the edge and decreases in line width by 0.5 μm every 4 mm for 12 mm inward, with the line width starting at 21 μm. EXAMPLES

[0103] This embodiment provides a method for manufacturing an all-black crystalline silicon solar cell, and the method includes the following steps (1) to (3).

[0104] (1) A film layer is deposited on the front surface of the silicon wafer 1 by the PECVD method (FIG. 1). The film layer has a laminated structure, and a silicon wafer with a front plated film is obtained. The film layer is formed from the innermost layer of SiN x Layer 2, middle SiN x Layer 3, SiO x N y Layer 4 and SiO x Layer 5 was laminated. The innermost layer was SiN x The thickness of layer 2 is 28 nm and the refractive index is 2.5. x Layer 5 is the outermost layer. It has a thickness of 25 nm and a refractive index of 1.55.

[0105] The method for depositing the film layer includes the following steps (a) to (e).

[0106] (a) After evacuation, silane and ammonia gases were pre-introduced under the condition of a constant pressure of 200 Pa. The time was 15 s, the flow rate of silane was 2200 sccm, the flow rate of ammonia gas was 9000 sccm, and the temperature was 400°C.

[0107] (b) The innermost layer of SiN on the front surface of silicon wafer 1 x Layer 2 is deposited with a deposition time of 60 s, a temperature of 600° C., a constant pressure of 200 Pa, a silane flow rate of 2200 sccm, an ammonia gas flow rate of 9000 sccm, an RF power of 14000 W, and a pulse on / off ratio of 5 / 70.

[0108] (c) Innermost layer: SiN x On top of layer 2 is a middle layer of SiN x Deposit layer 3, intermediate SiN x Layer 3: SiO x N y Layer 4 is deposited.

[0109] (d) After evacuation, silane and nitrous oxide were pre-introduced for 15 s under the conditions of a constant pressure of 150 Pa, a temperature of 400°C, and a flow rate of silane of 600 sccm and a flow rate of nitrous oxide of 10,000 sccm.

[0110] (e)SiO x Ny Layer 4: SiO x Layer 5 is deposited with a time of 190 s, a temperature of 500° C., a constant pressure of 130 Pa, a silane flow rate of 600 sccm, a nitrous oxide flow rate of 10000 sccm, an RF power of 14000 W, and a pulse on / off ratio of 1 / 30.

[0111] (2) The resulting silicon wafer with the front plated film is subjected to backside PECVD and laser grooving to obtain crude silicon solar cells.

[0112] (3) After screen printing and electrical injection are performed on the obtained crude silicon solar cell, the all-black crystalline silicon solar cell is obtained.

[0113] The screen printing method includes putting in the wafer and grooving, then printing the first time and drying, printing the second time and drying, printing the third time and drying, and using a line width gradation type screen to print the fourth time and drying, firing, testing the line width of the battery, and then completing the screen printing.

[0114] The graduated line width screen starts at the edge and decreases in line width by 1 μm every 5 mm for 15 mm inward, with the line width at the starting position being 19 μm. EXAMPLES

[0115] This embodiment provides a method for manufacturing an all-black crystalline silicon solar cell, and the innermost layer of SiN x The same as in Example 1, except that the refractive index of the layer is 2. EXAMPLES

[0116] This embodiment provides a fabrication method for an all-black crystalline silicon solar cell, and uses SiO x Same as Example 1, except that the refractive index of the layer is 1.3. EXAMPLES

[0117] This embodiment provides a fabrication method for an all-black crystalline silicon solar cell, and uses SiO x It is the same as Example 1, except that the refractive index of the layer is 1.6. EXAMPLES

[0118] This embodiment provides a method for manufacturing an all-black crystalline silicon solar cell, which is the same as embodiment 1, except that in step (3), the graded linewidth screen is not adopted but is replaced with a normal screen. EXAMPLES

[0119] This embodiment provides a method for manufacturing an all-black crystalline silicon solar cell, and the innermost layer of SiN x Same as Example 1, except that the layer thickness is 55 nm. EXAMPLES

[0120] This embodiment provides a fabrication method for an all-black crystalline silicon solar cell, and uses SiO x Same as Example 1, except that the layer thickness is 15 nm. EXAMPLES

[0121] This embodiment provides a fabrication method for an all-black crystalline silicon solar cell, and uses SiO x Same as Example 1, except that the layer thickness is 45 nm.

[0122] [Comparative Example 1] This comparative example provides a method for manufacturing an all-black crystalline silicon solar cell, and the innermost layer of SiN x Same as Example 1, except that the layer thickness is 15 nm.

[0123] [Comparative Example 2] This comparative example provides a method for manufacturing a silicon solar cell, and the method is obtained according to CN204497240U.

[0124] The solar cells obtained by the above manufacturing method were tested and the results are shown in Table 1 below.

[0125] [Table 1]

[0126] From Table 1 above, the following conclusions can be drawn:

[0127] (1) From Examples 1 to 3, it was found that the manufacturing method according to the present application affects the absorption and reflection effects of incident light on the cell surface, so that the incident light is almost completely absorbed and a very small amount is reflected, resulting in an all-black silicon crystal solar cell, which further has high conversion performance.

[0128] (2) Comparing Example 4 with Example 1, the innermost layer of SiN x It has been found that if the refractive index of the layer is not 2.3 or more, the black effect of the manufactured all-black crystalline silicon solar cell is poor.

[0129] (3) From the comparison of Examples 5 and 6 with Example 1, SiO x It has been found that if the refractive index of the layers is not within the range of 1.45 to 1.55 according to the present application, the black effect of the manufactured all-black crystalline silicon solar cell is poor.

[0130] (4) Comparing Example 7 with Example 1, it can be seen that when the gradated line width screen of the present application is not used, the periphery of the manufactured all-black crystalline silicon solar cell appears blue.

[0131] (5) Comparing Example 8 with Example 1, the innermost layer of SiN x It was found that when the layer thickness was greater than 55 nm, the black effect of the fabricated all-black crystalline silicon solar cells was poor.

[0132] (6) From a comparison of Examples 9 and 10 with Example 1, SiO x It was found that if the layer thickness was not within the range of 20-40 nm, the black effect of the manufactured all-black crystalline silicon solar cells was poor.

[0133] (7) From a comparison between Comparative Example 1 and Example 1, the innermost layer of SiN x It has been found that if the layer thickness is not 20 nm or more according to the present application, the black effect of the manufactured all-black crystalline silicon solar cell is poor.

[0134] (8) Comparison between Comparative Example 2 and Example 1 reveals that the improvements in the related art of the present application improve the black effect and conversion efficiency of the all-black crystalline silicon solar cell.

[0135] Although the present application has described the detailed structural features of the present application through the above embodiments, the present application is not limited to the above detailed structural features, that is, it does not mean that the present application must be implemented depending on the above detailed structural features. Those skilled in the art should understand that any improvements to the present application, equivalent replacements and addition of auxiliary parts to the members used in the present application, selection of specific forms, etc. are all within the scope of protection and disclosure of the present application.

Claims

1. The innermost layer of a laminated structure, a SiN layer with a thickness of 25 to 50 nm and a refractive index of 2.8 to 3.4, is deposited on the front surface of a silicon wafer by the PECVD method. x (1) depositing a membrane layer including a layer to obtain a front coated silicon wafer; (2) performing backside PECVD and laser grooving on the resulting front side coated silicon wafer to obtain crude silicon solar cells; (3) performing screen printing and electrical injection on the obtained crude silicon solar cell to obtain an all-black crystalline silicon solar cell; The screen printing method includes: after grooving, performing a first printing and drying, performing a second printing and drying, performing a third printing and drying, performing a fourth printing and drying, firing, testing the line width of the battery, and then completing the screen printing, the error of the test of the line width of the battery is less than 5 μm, the fourth printing is performed by extrusion printing using a line width gradation type screen, and the line width of the line width gradation type screen decreases in a gradient from the outside to the inside. How all-black crystalline silicon solar cells are made.

2. The film layers described in step (1) are the innermost layer of SiN x layer, intermediate SiN x layer, SiO x N y layer and SiO x Including layers, The method for producing the all-black crystalline silicon solar cell of claim 1 .

3. The outermost layer of the membrane layer described in step (1) is SiO x Including layers, The method for producing the all-black crystalline silicon solar cell of claim 1 .

4. The SiO x The layer thickness is 20 nm or more. The method for producing the all-black crystalline silicon solar cell according to claim 3.

5. The SiO x The layer thickness is 20-40 nm. The method for producing the all-black crystalline silicon solar cell of claim 4.

6. The SiO x The refractive index of the layer is between 1.45 and 1.55; The method for producing the all-black crystalline silicon solar cell according to claim 3.

7. The deposition morphology described in step (1) is (a) pre-introducing silane and ammonia gases under constant pressure after evacuation; The innermost layer of SiN on the front of the silicon wafer x (b) depositing a layer; Innermost layer: SiN x An intermediate SiN layer is formed on the x A layer is deposited, and the intermediate SiN x On top of the layer x N y (c) depositing a layer; (d) pre-introducing silane and nitrous oxide under constant pressure conditions after evacuation; SiO x N y On top of the layer x and (e) depositing a layer. The method for producing the all-black crystalline silicon solar cell of claim 2.

8. The constant pressure described in step (a) is 200 to 250 Pa; The method for producing the all-black crystalline silicon solar cell of claim 7.

9. The time of pre-introduction described in step (a) is 15 to 30 s; The method for producing the all-black crystalline silicon solar cell of claim 7.

10. The pre-introduction flow rate of silane described in step (a) is 2200 to 2500 sccm; The method for producing the all-black crystalline silicon solar cell of claim 7.

11. The preliminary introduction flow rate of ammonia gas described in step (a) is 9000 to 9300 sccm; The method for producing the all-black crystalline silicon solar cell of claim 7.

12. The temperature of the pre-introduction described in step (a) is 400 to 600° C.; The method for producing the all-black crystalline silicon solar cell of claim 7.

13. The duration of deposition according to step (b) is 60-80 s; The method for producing the all-black crystalline silicon solar cell of claim 7.

14. The temperature of the deposition according to step (b) is between 400 and 600° C.; The method for producing the all-black crystalline silicon solar cell of claim 7.

15. The pressure of the deposition described in step (b) is 200-250 Pa; The method for producing the all-black crystalline silicon solar cell of claim 7.

16. introducing silane and ammonia gases during the deposition process described in step (b); The method for producing the all-black crystalline silicon solar cell of claim 7.

17. The flow rate of the silane is 2200 to 2500 sccm.

17. The method of claim 16 for producing an all-black crystalline silicon solar cell.

18. The flow rate of the ammonia gas is 9000 to 9300 sccm.

17. The method of claim 16 for producing an all-black crystalline silicon solar cell.

19. The RF power of the deposition process described in step (b) is 14000-16000 W; The method for producing the all-black crystalline silicon solar cell of claim 7.

20. The on / off ratio of the pulses in the deposition process described in step (b) is (3-5) / (50-70); The method for producing the all-black crystalline silicon solar cell of claim 7.

21. The constant pressure described in step (d) is 150 to 200 Pa; The method for producing the all-black crystalline silicon solar cell of claim 7.

22. The time of pre-induction described in step (d) is 5 to 15 s; The method for producing the all-black crystalline silicon solar cell of claim 7.

23. The pre-introduction flow rate of silane described in step (d) is 600 to 700 sccm; The method for producing the all-black crystalline silicon solar cell of claim 7.

24. The preliminary introduction flow rate of nitrous oxide described in step (d) is 10,000 to 12,000 sccm; The method for producing the all-black crystalline silicon solar cell of claim 7.

25. The temperature of the pre-introduction described in step (d) is 400 to 600° C.; The method for producing the all-black crystalline silicon solar cell of claim 7.

26. The duration of deposition described in step (e) is 150-200 s; The method for producing the all-black crystalline silicon solar cell of claim 7.

27. The temperature of the deposition according to step (e) is between 400 and 600° C.; The method for producing the all-black crystalline silicon solar cell of claim 7.

28. The pressure of the deposition described in step (e) is 100 to 150 Pa; The method for producing the all-black crystalline silicon solar cell of claim 7.

29. introducing silane and nitrous oxide during the deposition process described in step (e); The method for producing the all-black crystalline silicon solar cell of claim 7.

30. The flow rate of the silane is 600 to 700 sccm.

30. The method of claim 29 for producing an all-black crystalline silicon solar cell.

31. The flow rate of the nitrous oxide is 10,000 to 12,000 sccm.

30. The method of claim 29 for producing an all-black crystalline silicon solar cell.

32. The RF power of the deposition process described in step (e) is 14000-16000 W; The method for producing the all-black crystalline silicon solar cell of claim 7.

33. The on / off ratio of the pulses of the deposition process described in step (e) is (1-3) / (30-50); The method for producing the all-black crystalline silicon solar cell of claim 7.

34. The line width of the graduated line width screen decreases by at most 1 μm every at most 5 mm from the outer edge toward the inside. The method for producing the all-black crystalline silicon solar cell of claim 1 .

35. The accuracy of the line width gradation screen is ±1 μm; The method for producing the all-black crystalline silicon solar cell of claim 1 .

Citation Information

Patent Citations

  • Solar cell multi-layer anti-reflection grading film and preparation method thereof

    CN110391304A

  • Solar cell for all-black crystalline silicon photovoltaic module and preparation method of solar cell

    CN111106186A

  • Solar cell, preparation method thereof and multilayer composite passivation film on back surface of solar cell

    CN112531035A

  • Polycrystalline silicon solar battery assembly

    CN202513162U

  • Solar cell's antireflection coating production facility, antireflection coating and solar cell

    CN208701204U